2017
DOI: 10.1016/j.jplph.2017.03.010
|View full text |Cite
|
Sign up to set email alerts
|

Brachytic 1 of barley (Hordeum vulgare L.) encodes the α subunit of heterotrimeric G protein

Abstract: Physiological and molecular biological analysis of the dwarf barley (Hordeum vulgare L.) mutant brachytic 1 (brh1) was conducted. The root responses of brh1 to brassinolide were weaker than those of wild type, but the responses of leaf segments of dark-grown plants were not. Responses of brh1 to gibberellin A were similar to or slightly stronger than those of wild type. Endogenous levels of these hormones in young seedlings were not clearly different between brh1 and wild type. Skotomorphogeneses of brh1 were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 38 publications
(64 reference statements)
0
3
0
Order By: Relevance
“…Recently, Ito et al () explored the barley Brh1 locus and identified some mutants resembling the rice dwarf mutant, daikoku ( dwarf1 ; d1 ) (Akemin ; Kadam ). The daikoku mutant has a mutation in the heterotrimeric G protein α subunit (Gα) (Ashikari et al , Fujisawa et al ).…”
Section: Genetics Of Barley Shoot Architecturementioning
confidence: 99%
“…Recently, Ito et al () explored the barley Brh1 locus and identified some mutants resembling the rice dwarf mutant, daikoku ( dwarf1 ; d1 ) (Akemin ; Kadam ). The daikoku mutant has a mutation in the heterotrimeric G protein α subunit (Gα) (Ashikari et al , Fujisawa et al ).…”
Section: Genetics Of Barley Shoot Architecturementioning
confidence: 99%
“…RGA1 mediates a crosstalk between the BR and GA signaling pathways [ 299 ]. Recently, the barley Brachytic1 gene, which encodes the alpha subunit of the heterotrimeric G protein has been identified and functionally analyzed [ 319 , 320 ].…”
Section: Br Signaling In Cereal Crops—novel and Specific Componentmentioning
confidence: 99%
“…Potential partners linking meristem maintenance and stem elongation, especially in response to environmental cues, are heterotrimeric G‐proteins. For instance, a major dwarfing locus in rice, DENSE PANICLE1 (DEP1) and barley ( HvDEP1 ) encodes a Gγ subunit (Huang et al ; Wendt et al ; Xu et al ) while defective alleles in genes encoding the Gα subunit in rice (‘ daikoku ’ dwarf1 , Ashikari et al ; Fujisawa et al ), barley ( brachytic1 , Ito et al ; Braumann et al ), maize ( compact plant2 , ct2 , Bommert et al ) and Arabidopsis ( gpa1 , Ullah et al ) confer compact shoots due to reduced axial proliferation. In rice, DWARF1 interacts with GA and BR signaling to control height (Ashikari et al ; Oki et al ).…”
Section: Regulation Of Subapical Proliferationmentioning
confidence: 99%